Central retinal vein occlusion following Sirsasana (headstand posture) - Shah Nikunj; Shah Urmi (Indian Journal of Ophthalmology, 2009)
We report a case of central retinal vein occlusion (CRVO) following Sirsasana, a head-down postural yoga. A 55-year-old male patient presented to us, with sudden-onset loss of vision following Sirsasana, in the right eye. The patient had suffered from pulmonary thromboembolism 5 years earlier and was receiving warfarin prophylaxis. Over 6 months of follow-up, the patient developed neovascularization of the iris and was subjected to panretinal laser with no improvement in visual acuity. Sirsasana could be an important risk factor for CRVO especially in predisposed patients.